2004
DOI: 10.4049/jimmunol.173.3.2109
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Arginase in a Mouse Model of Colitis

Abstract: Arginase is the endogenous inhibitor of inducible NO synthase (iNOS), because both enzymes use the same substrate, l-arginase (Arg). Importantly, arginase synthesizes ornithine, which is metabolized by the enzyme ornithine decarboxylase (ODC) to produce polyamines. We investigated the role of these enzymes in the Citrobacter rodentium model of colitis. Arginase I, iNOS, and ODC were induced in the colon during the infection, while arginase II was not up-regulated. l-Arg supplementation of wild-type mice or iNO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
129
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 112 publications
(147 citation statements)
references
References 45 publications
(43 reference statements)
16
129
2
Order By: Relevance
“…We establish that the host innate immune response represses EHEC virulence, with this particular insight that NO does not directly kill the pathogen but decreases the production of a toxin. Thus, increasing NO production in infected patients, by using NO donor or L-arginine treatment (39), might represent an alternative strategy to limit the development of HUS. Moreover, we propose that differential NO production in infected patients could represent a marker of host susceptibility for EHEC infection.…”
Section: Discussionmentioning
confidence: 99%
“…We establish that the host innate immune response represses EHEC virulence, with this particular insight that NO does not directly kill the pathogen but decreases the production of a toxin. Thus, increasing NO production in infected patients, by using NO donor or L-arginine treatment (39), might represent an alternative strategy to limit the development of HUS. Moreover, we propose that differential NO production in infected patients could represent a marker of host susceptibility for EHEC infection.…”
Section: Discussionmentioning
confidence: 99%
“…123 In addition, infection with Citrobacter rodentium was shown to cause a significant decrease in serum LArg concentration with associated infection-induced immunopathology that was partially reversed after L-Arg supplementation. 124 Although, their distinct contribution remains to be explored, it is likely that altered activities of L-Arg catabolizing enzyme families, Arg as well as NOS all contribute to the observed intestinal immunopathologies. It therefore can be postulated that Arg activity through conversion of L-Arg into L-Orn enhances intestinal epithelial barrier function, 125 while iNOS activity confers an antiinflammatory state through regulation of energy metabolism.…”
Section: Ly6gmentioning
confidence: 99%
“…3 A further issue for consideration is what is the specificity of the c-Myc and ODC response to H. pylori in macrophages? For comparison, we have studied the Gram-negative enteric pathogen Citrobacter rodentium, which causes colitis in mice (22), and the effect of the chemical inducer of apoptosis, staurosporine, and found that both agents cause apoptosis in macrophages without inducing ODC or c-Myc (data not shown). Additionally, inhibition of H. pylori-induced apoptosis with catalase or cyclosporine A did not prevent induction of ODC or c-Myc (data not shown), indicating that the process of apoptosis itself is not required to stimulate this pathway of polyamine generation.…”
Section: C-myc In H Pylori-induced Macrophage Apoptosismentioning
confidence: 99%